Study on quantitative characterization of microscopic pore throat in tight oil reservoir - Zheng, Xiaomei; Qiu, Xiangliang; Wang, Zhengquan; He, Xin; Li, Sunyi; Tan, Chengqian; Pan, Jingyu; Luo, Xiang (Frontiers in Earth Science, 2025)
Tight oil reservoirs exhibit poor physical properties, significant heterogeneity, and intricate pore structures. The investigation of the microscopic pore-throat structure plays a pivotal role in assessing the efficacy of these reservoirs. Using the Chang 8 reservoir in the Yanchi area of the Ordos Basin as a case study, conventional experimental methods were used to analyze and test its pore structure and evaluate the micro pore structure characteristics of the reservoir in this area, but due to the large amount of experimental data obtained by the conventional experimental methods and the difficulty of analyzing them, so we proposed a method of logging and evaluating the quality of the microscopic pore throats. By carrying out the research on the quantitative characterization relationship between the microscopic pore structure parameters and microscopic pore-throat quality of the tight reservoir, the pore-throat quality logging evaluation index PTI was obtained, and the quantitative evaluation standard of microscopic pore-throat quality of the tight sandstone reservoir was established. The findings indicate the following: (1) The predominant pore types within the Chang 8 reservoir in the study region consist mainly of intergranular pores and feldspar dissolved pores, showing an average surface porosity of 3.3%. The reservoir predominantly comprises nano-scale pore throats, contributing to its dense nature. Fluid seepage capacity is primarily governed by relatively larger pores. The main throat radius falls within the range of 101–601 nm, with an average pore throat ratio mainly ranging between 102 and 199. The average movable fluid saturation is measured at 26.51%. (2) After thorough analysis, it has been discerned that four key parameters—porosity (φ), median radius (Rpt50), displacement pressure (Pd), and maximum pore throat radius (Rmax)—exert significant influence on pore throat quality. Consequently, a logging evaluation index, PTI (Pore Throat Index), has been devised to gauge pore throat quality, accompanied by the establishment of a quantitative evaluation standard for the microscopic pore throat quality of tight sandstone reservoirs. (3) The reservoirs within the research area are categorized into four groups: I, II, III, and IV. A higher PTI value indicates superior pore throat quality, leading to an overall enhanced reservoir evaluation. This quantitative evaluation method is of guiding significance for the quantitative characterization of micropore throats in tight oil reservoirs and the efficient development of the oil field in this area, and it is also of some reference significance for the quantitative characterization of micropore throats in similar tight sandstone reservoirs.